Soil mounding practices on performances of oil palm in peat soil in P.T. Nafasindo Acheh Singkil, Indonesia / Nurul Farahana Hazira Hazlee - Hazira Hazlee, Nurul Farahana (Faculty of Plantation and Agrotechnology, 2016)
The secondary data has been taken at P.T Nafasindo Acheh Singkil, Indonesia during semester break. The data was analysed by using Sigma Plot and Microsoft Excel software. Soil mounding application is one of the best management practices that can help to increase the oil palm production in peat area. The peat soils are high in organic matter and have very fertile soil for oil palm cultivation (Murtedza et al, 2002). The tendency of the oil palm become lean and falling down are very high, if the oil palms are planted in the peat soil area. The roots of the palm tree also will appear on the ground of the soil surface. So, these practices have been done to prevent the oil palm become lean and falling down. Furthermore, these practices can enhance root growth and the root can uptake enough nutrient for the oil palm uptake. The result of this study this study was indicated that there is a significant difference in the yield and nutritive value of the oil palm when soil mounding is applied.